KEPRIBADIAN PENDIDIK: TELAAH PSIKOLOGI ISLAMI - Idi Warsah; Muhamad Uyun (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2019)
The discussion of educator behavior has been studied in many studies both from literature and empirical studies, but so far there have been no studies that specifically examine the personality of educators needed by the present education process in terms of aspects of Islamic Psychology. Departing from the search above, this article aims to conduct a study of this matter. Based on the review and analysis of the content of the literature used as a reference for this study, it was concluded that, to become a complete education each educator must have a personality such as: always draw closer to God in any situation or condition; master extensive knowledge; smart, honest, safe in carrying out their duties, patient and sincere in guiding students, creative in choosing learning methods, can be role models, open to krikit, authoritative, fair, non-discriminatory, pleasant, and polite speech. This personality can be referred to as your sainthood in Islamic psychology, which is a personality that is bound by a strong belief in God by carrying out religious teachings.